KAJIAN MENEJEMEN SPECIAL EVENT GOLDBLATT DALAM ROAD SHOW SANTRI SEHAT oleh PT BIO FARMA - Feliza Zubair; Dara Anjani Shahidah (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
This study aims to describe the stage of the research, design, planning, coordination, andevaluation conducted by Corporate Communication of PT Bio Farma (Persero) at the Roadshow"Healthy Students" program. The method used a descriptive method with qualitative researchapproaches. Data collection methods used interviews, observation, literature study anddocumentation. The results of this study showed that the forms of research through informalresearch by searching the secondary data to determine the target audience, the concept and themeof the event is appropriate and in accordance with existing conditions, namely "Santri Sehat"embodied in the design, lighting, color and performers , Internal meetings are conducted onlythree times to communicate and coordinate to discuss preparations for implementation of theactivities. In the evaluation, the results of the implementation of the roadshow are reviewedannually by questionnaire. Based on the results of questionnaires known that more than 70% ofthe participants already have a good knowledge about the vaccine and its benefits. Through thisstudy, the researchers suggested that the situation analysis carried out by the formal and informalapproaches to search the data directly in the field, more attention to media publications oninternal company events, and reviewing the most effective time to measure basic knowledge aboutthe vaccine and its benefits.